2017
DOI: 10.3390/ijms18122706
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Markers for Interspecies Transmission of Avian Influenza Viruses in Mammalian Hosts

Abstract: In the last decade, a wide range of avian influenza viruses (AIVs) have infected various mammalian hosts and continuously threaten both human and animal health. It is a result of overcoming the inter-species barrier which is mostly associated with gene reassortment and accumulation of mutations in their gene segments. Several recent studies have shed insights into the phenotypic and genetic changes that are involved in the interspecies transmission of AIVs. These studies have a major focus on transmission from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 161 publications
(246 reference statements)
1
32
0
Order By: Relevance
“…Studies have shown that some mutations known to enhance the transmissibility of H5N1 HPAI viruses may increase the ability of LPAI viruses to be transmitted from bird to marine mammal ( 11 13 ). These factors include the change of sialic acid receptor binding affinity ( 11 ) and adaptive mutations in the vRNP complex for replication and virus spread in the seal population ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that some mutations known to enhance the transmissibility of H5N1 HPAI viruses may increase the ability of LPAI viruses to be transmitted from bird to marine mammal ( 11 13 ). These factors include the change of sialic acid receptor binding affinity ( 11 ) and adaptive mutations in the vRNP complex for replication and virus spread in the seal population ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…All available information on AIV molecular markers/mutations was collected from: the CDC H5N1 Genetic changes inventory [17], the WHO Working Group on Surveillance of Influenza Antiviral Susceptibility (WHO-AVWG) [18], and publications summarizing AIV mutations and molecular markers affecting biological characteristics and potential risk [1921]. Journal articles were sourced for each specific subtype using PubMed searches with MeSH Terms, Boolean operators and wild cards.…”
Section: Methodsmentioning
confidence: 99%
“…However, the species barrier can be broken by some AIV subtypes which can infect humans [ 5 , 6 ]. At least eight AIV subtypes have been reported to infect humans, resulting in human influenza pandemics (H1, H2, H3, H5, H6, H7, H9, and H10) [ 7 , 8 ]. Prior to 2013, H5N1, H5N2, H7N2, H7N3, H7N7, H9N2, and H10N7 AIVs were known to cause human infection, then H7N9, H6N1, H10N8, and H5N6 AIVs were also detected in humans [ 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%